'I can't put that on paper.' How medical professional values shape the content of death certificates. Issue 2 (22nd June 2016) - Leslie, Myles
Abstract: This paper follows collegiality, demonstrating how, as a central value of medically trained coroners, it can shape the content of death investigations and certificates. Drawing on ethnographic evidence from a 16-month-long study of the Office of the Chief Coroner (OCC) of Ontario, Canada, I argue that collegiality is an instrument of trust that both affords investigators tremendous access to information, and severely limits the flow of that information into the public domain that the OCC serves. The paper focuses on in-care death investigations, which are those where the OCC's medically qualified coroners find themselves investigating the quality of care delivered by professional colleagues. I show how professional expertise, experience and collegial values often combine to see instances of poor or even incompetent care dealt with privately (rather than publicly) or referred up the medical (rather than public safety) hierarchy. The burden of my argument is that collegial deference to the autonomy and skills of other physicians tends to see coroners expurgate the death certificates they produce. These expurgations obscure competence issues from public view and reduce the accuracy of the certificates. I close with a discussion of the benefits and drawbacks of medically qualified death investigators, as well as potential adjustments to improve the accuracy of in-care death investigations and certifications.